2015
DOI: 10.1002/ajmg.a.37026
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language in a genotyped cohort of individuals with Kabuki syndrome

Abstract: Speech and language deficits are commonly associated with Kabuki syndrome. Yet little is known regarding the specific symptomatology of these disorders, preventing use of targeted treatment programs. Here we detail speech and language in 16 individuals with Kabuki syndrome (thirteen with KMT2D mutations, one with a KDM6A mutation, and two mutation-negative cases), aged 4-21 years. The most striking speech deficit was dysarthria, characterised by imprecise consonants, harsh vocal quality, hypernasality, reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
4
29
0
1
Order By: Relevance
“…Concerning the nature of linguistic impairment, our hypothesis is in accordance with Morgan et al. () that studied a cohort with molecularly confirmed diagnosis of KS and suggested that linguistic deficit is not the key feature of the syndrome but instead may be the result of the neurological, orofacial structural, hearing, and cognitive deficit in KS. Regarding speech, our results indicated that phonological disorder and oromotor dysfunction characterized more than half of our participants (71% and 69% of cases, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Concerning the nature of linguistic impairment, our hypothesis is in accordance with Morgan et al. () that studied a cohort with molecularly confirmed diagnosis of KS and suggested that linguistic deficit is not the key feature of the syndrome but instead may be the result of the neurological, orofacial structural, hearing, and cognitive deficit in KS. Regarding speech, our results indicated that phonological disorder and oromotor dysfunction characterized more than half of our participants (71% and 69% of cases, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…In these studies, behavioral problems, including hyperactivity and attention deficit disorder, have been reported to recur in a small fraction of affected subjects. More recently, genotype–phenotype correlation analyses focused on the nature and frequency of speech and language deficits in a relatively small cohort of patients have documented a heterogeneous pattern of oromotor, speech and linguistic impairment (Morgan et al., ). Oromotor deficits and dysarthria have been described as a consistent phenotypic feature in patients with KS, and articulation, phonological development, and receptive and expressive linguistic domains were found affected in the majority of cases included in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous mutations in the SCN9A gene have previously been associated with generalized epilepsy with febrile seizures (OMIM#613863) and Dravet syndrome (severe myoclonic epilepsy of infancy, OMIM#607208) when accompanied by mutations in the SCN1A (Sodium channel, neuronal type 1, alpha subunit, OMIM*182389) gene5455. Loss-of-function mutations in KMT2D have been reported to cause Kabuki syndrome (OMIM#147920)565758, a severe syndromic form of intellectual disability associated with dysarthria and oromotor deficits, microcephaly and nystagmus59. The KMT2D variants in our cohort were rare nonsynonymous changes, rather than confirmed loss-of-function mutations, and the individuals who carried them did not show features of Kabuki syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…SCN9A has been associated with febrile epileptic seizures, which themselves carry an increased risk of language impairment67. Heterozygous loss-of-function mutations of the KMT2D gene are implicated in Kabuki syndrome, a severe developmental syndrome that often presents with heterogeneous oromotor, speech, and language deficits59. The KMT2D variants we identified are nonsynonymous changes that may alter protein properties but are very unlikely to act as fully penetrant loss-of-function alleles, especially given that carriers of these variants do not suffer from Kabuki syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Intellectual disability and additional handicaps made it difficult to develop receptive and expressive language skills after implantation [6] , besides impairments across the areas of language, speech, and oro-motor functions in patients with KS [7] . Regardless of whether a child has a hearing loss only or has a disability in addition, there is a relationship between increased age at implantation and poor performance [8] .…”
Section: Discussionmentioning
confidence: 99%